The Use of (14)C-FIAU to Predict Bacterial Thymidine Kinase Presence: Implications for Radiolabeled FIAU Bacterial Imaging - Peterson Kristin, L (2013)
Currently available infectious disease imaging techniques cannot differentiate between infection and sterile inflammation or between different types of infections. Recently, radiolabeled FIAU was found to be a substrate for the thymidine kinase (TK) enzyme of multiple pathogenic bacteria, leading to its translational use in the imaging of bacterial infections. Patients with immunodeficiencies, however, are susceptible to a different group of pathogenic bacteria when compared to immunocompetent subjects. In this study, we wanted to predict the usefulness of radiolabeled FIAU in the detection of bacterial infections commonly occurring in patients with immunodeficiencies, in vitro, prior to attempting in vivo imaging with (124)I-FIAU-PET. METHODS: We obtained representative strains of bacterial pathogens isolated from actual patients with genetic immunodeficiencies. We evaluated the bacterial susceptibility of different strains to the effect of incubation with FIAU, which would implicate the presence of the thymidine kinase (TK) enzyme. We also incubated the bacteria with (14)C-FIAU and consequently measured its rate of incorporation in the bacterial DNA using a liquid scintillation counter. RESULTS: Unlike the other bacterial strains, the growth of Pseudomonas aeruginosa was not halted by FIAU at any concentration. All the tested clinical isolates demonstrated different levels of (14)C-FIAU uptake, except for P. aeruginosa. CONCLUSION: Radiolabeled FIAU has been successful in delineating bacterial infections, both in preclinical and pilot translational studies. In patients with immunodeficiencies, Pseudomonas infections are commonly encountered and are usually difficult to differentiate from fungal infections. The use of radiolabeled FIAU for in vivo imaging of those patients, however, would not be useful, considering the apparent lack of TK enzyme in Pseudomonas. One has to keep in mind that not all pathogenic bacteria possess the TK enzyme and as such will not all retain FIAU. Our technique is simple, and can be easily used to assess whether a certain bacterial strain of interest can or cannot be visualized using radiolabeled FIAU.